Service Marketing, Referral Marketing, and Trust Icon Corporate to Increase Customer Satisfaction - Farhan Arya Indrajaya; Tri Siwi Agustina (Indonesian Business Review, 2023)
Entrepreneurs must pay attention to customer satisfaction in their corporate environment and drive corporate strategies to increase turnover and achieve the company's core goals. So this research is here to provide new concepts relevant to the current situation and conditions. This study aims to reveal the effect of service marketing, referral marketing, and corporate trust icons on customer satisfaction. The method used is quantitative by promoting partial least squares (PLS) in proving the proposed hypothesis. Then, the sample used was 100 consumers at a company in Gresik. The findings of this study demonstrate that service marketing, referral marketing, and corporate trust icons have a positive and significant effect on customer satisfaction. Theoretical and practical implications are also discussed in this study.